2005
DOI: 10.3354/meps289131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilayella littoralis on Fucus vesiculosus recruitment: implications for community composition

Abstract: With increasing eutrophication in coastal areas, mass developments of annual filamentous algae, such as Pilayella littoralis and Enteromorpha spp., have increased. Simultaneously, the perennial macroalga Fucus vesiculosus has declined in many areas in the Baltic Sea. To test the effects of P. littoralis on F. vesiculosus we performed a number of laboratory and field studies. The most severe negative effect observed was the reduced number of settled germlings (95%) when P. littoralis was present on the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In addition, the high tolerance of R. atra to wide variations in salinity and temperature in the upper intertidal zone compared with the other macroalgal species such as Laurencia optusa and the probable ability of P. opaca in lower intertidal zone to secrete allellopathic compounds might contribute to the marked competing activity of the two species. This agrees with Råberg et al (2005) who reported that, the exudates from Polysiphonia species appear to exert a negative effect on the reproduction of Fucus vesiculosus. These alien species might represent greater threat to native biodiversity than do pollution in the study area since…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the high tolerance of R. atra to wide variations in salinity and temperature in the upper intertidal zone compared with the other macroalgal species such as Laurencia optusa and the probable ability of P. opaca in lower intertidal zone to secrete allellopathic compounds might contribute to the marked competing activity of the two species. This agrees with Råberg et al (2005) who reported that, the exudates from Polysiphonia species appear to exert a negative effect on the reproduction of Fucus vesiculosus. These alien species might represent greater threat to native biodiversity than do pollution in the study area since…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, surface siltation has been found to be stressful to both filter feeders (Seed & Suchanek 1992, Dame 1996 and macroalgae (Wallentinus 1976, Eriksson 2002, Berger et al 2003. Also, filamentous macroalgae may overgrow and negatively influence the underlying community by shading (Rohde et al 2008), causing anoxic conditions while decaying (Paalme et al 2002) and impairing settling, recruitment and early survival of other species (Berger et al 2003, Råberg et al 2005, Qvarfordt 2006). Water movement keeps the substrate clean (Kautsky 1988) and more efficiently removes loosely attached macroalgae from the substrate at wave-exposed compared to sheltered locations, and may thereby influence the recruitment and growth of different benthic species.…”
Section: Permanovamentioning
confidence: 99%
“…When P. littoralis is present on the substrate prior to seeding of F. vesiculosus eggs, the recruitment of F. vesiculosus germlings is reduced (Råberg et al 2005). Allelopathy may be involved as exudates from P. littoralis affect F. vesiculosus negatively: a low concentration of exudates reduce the attachment rate, while higher concentrations hamper germination and rhizoid development (Råberg et al 2005).…”
Section: Allelopathy In Space Competition and In Resisting Epibiotismmentioning
confidence: 99%
“…Allelopathy may be involved in competitive success of bloom-forming macroalgae (Nelson et al 2003;Råberg et al 2005). Nelson et al (2003) studied toxic properties of two common "green tide" seaweeds Ulva fenestrata and Ulvaria obscura.…”
Section: Allelopathy In Space Competition and In Resisting Epibiotismmentioning
confidence: 99%
See 1 more Smart Citation